World Economy Winter 2021 - Temporary slowdown - Klaus-Jürgen Gern; Stefan Kooths; Jan Reents; Ulrich Stolzenburg (Kiel Institute for the World Economy (IfW Kiel), 2021)
Following an encouraging first half of the year, the recovery of the global economy has lost momentum. Across the globe, resurging Covid-19 infections weighed on economic activity. Supply chain disruptions prevented a further expansion of global industrial production, and the fast-moving recovery of the Chinese economy almost came to a sudden stop. The impact that the Omicron variant of the coronavirus will have on output remains uncertain at this stage. Over the next few months, we expect economic growth to be rather subdued before picking up again in 2022. We forecast global output (measured on a purchasing power parity basis) to increase by 5.7 percent in 2021 and 4.5 percent in 2022, representing a downward revision of our previous forecast by 0.2 and 0.5 percentage points for 2021 and 2022, respectively. For 2023, we have increased our forecast modestly from 3.8 percent to 4.0 percent. Inflation is thought to have peaked as the contribution of the energy component to overall inflation is expected to decline considerably going forward. Nonetheless, upward pressures on prices are expected to persist given continued supply constraints, and inflation rates will likely remain well above their respective pre-Covid levels.
Keywords: 330; advanced economies; emerging economies; monetary policy; COVID19